Effect of Combined or Separate Administration of Beta Carotene-Vitamin E and hCG on Fertility in Sheep Lambs - M. Ferit Özmen; Erkan Say; Ümüt Cirit (Journal of Agricultural Sciences)
This study was performed to investigate the effect of beta carotene-vitamin E and hCG treatments alone or a combination of both on fertility in estrus synchronized Awassi ewe lambs. A total of 103 Awassi ewe lambs were divided into four groups before the study. Lambs were treated with a progesterone sponge for 12 days, PGF2α two days before sponge removal, 600 IU PMSG on sponge removal day, and 150 IU hCG on the day of mating. The control group (n: 25) did not receive any additional treatment. The Vitamin group (β carotene + vitamin E) (n: 26) was treated twice with vitamin combination. The first treatment was on the 7th day before the sponge insertion and the second treatment was on the day of mating. The hCG group (n: 24) was treated with 150 IU hCG on day 12 after mating. The HCG + vitamin group (n: 28) was treated with both β carotene-vitamin E and hCG. Ewe lambs standing to be mounted were considered in estrus and mated. Pregnancy was determined by ultrasound the 30th day after the mating. There were no significant differences between the control and hCG, vitamin and hCG + vitamin groups concerning estrus, conception, lambing, abortion, twinning, fecundity rate, and litter size (P>0.05). It was concluded that the treatments with β-carotene-vitamin E and hCG or both, in addition to estrus synchronization out of the breeding season in Awassi ewe lambs did not improve the investigated fertility indices.